2018
DOI: 10.3892/etm.2018.6673
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMP-9 in different degrees of chronic hepatitis B and its correlation with inflammation

Abstract: Expression of matrix metalloproteinase-9 (MMP-9) in different degrees of chronic hepatitis B (CHB) and the correlation of MMP-9 with inflammation was investigated. A total of 96 CHB patients (observation group) admitted and treated in Dongying People's Hospital from December 2016 to November 2017 were selected, and they were compared with 60 healthy individuals (control group) selected in the physical examination center during the same time period. Enzyme-linked immunosorbent assay (ELISA) was used to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…MMP-9 is shown to regulate inflammation in different diseases. 10 12 Meanwhile, MMP-9 also remodels the extracellular matrix and controls the activity of numerous growth factors, cytokines, cell adhesion molecules and chemokines, which are essential in inflammation. 13 , 14 In sepsis, MMP-9 is associated with increased vascular permeability, which promotes inflammatory cell migration and regulates the crucial inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 is shown to regulate inflammation in different diseases. 10 12 Meanwhile, MMP-9 also remodels the extracellular matrix and controls the activity of numerous growth factors, cytokines, cell adhesion molecules and chemokines, which are essential in inflammation. 13 , 14 In sepsis, MMP-9 is associated with increased vascular permeability, which promotes inflammatory cell migration and regulates the crucial inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Frontiers in Medicine 05 frontiersin.org (23)(24)(25)(26). A link between MMP-9 and extracellular signal-regulated kinase (ERK) can be found in Schwann cells, and ERK involves in renal interstitial fibrosis, which is thought to be the final result of CKD (27).…”
Section: Discussionmentioning
confidence: 99%
“…IFNAR1 degradation can be promoted by either ligand binding and cellular signaling induced ubiquitination-dependent pathway, or Ser532 phosphorylation and p38 kinase activity requiring ligand-independent way ( 69 ). MMP-9 can be activated by HBV in CHB patients ( 70 , 71 ) and in turn facilitates HBV replication through attenuating IFN/JAK/STAT signaling, interacting with IFNAR1 to promoting its phosphorylation, ubiquitination, subcellular distribution, and degradation of IFNAR1 through lysosome pathways in Ser532 phosphorylation and p38 independent manner, as well as blocking its binding to IFN-α ( 39 ). However, a recent study found type I IFN strongly promotes the clearance of MMPs ( 72 ), thus, further study is needed to investigate the role of MMPs in the IFN-α therapy mediated antiviral efficacy against HBV infection.…”
Section: Negative Regulators In Ifn Induction and Signaling Pathwaymentioning
confidence: 99%